FOREIGN DIRECT INVESTMENTS AS A SOURCE OF SOUTHEAST EUROPEAN ECONOMIC DEVELOPMENT FINANCING - STOJANOVIC, DRAGICA MILORAD (Poslovna ekonomija, 2020)
The paper analyzes the sources of Southeast European countries economic development financing – Albania, Bosnia and Herzegovina, Bulgaria, Montenegro, Croatia, Romania, Macedonia, and Serbia from 2009 to 2018. The research focus is on the one hand directed towards the analysis of the economic growth rate, the share of domestic savings and the current account balance. On the other hand, particular emphasis in the analysis is given to the data on the dynamics of foreign direct investment. The analysis in the paper indicates that due to the lack of domestic savings and difficulties with foreign borrowing, in the observed period, foreign direct investment was the most represented source of financing for economic development. The analysis for the SEE countries also shows that the lack of domestic savings caused the unfavorable structure of foreign direct investment flows with the end result of a low economic growth rate. When it comes to the relevance of foreign direct investment for the long-term economic development of Southeast European countries, it concludes that a more active development policy is needed, aimed at increasing the share of domestic savings in gross domestic product as well as the growth of the domestic investment. Simply, in these circumstances, it is unrealistic to expect it to be just foreign investment. Key words: economic development, sources of financing, foreign direct investment, domestic savings, Southeast Europe